Near chromosome-level and highly repetitive genome assembly of the snake pipefish Entelurus aequoreus (Syngnathiformes: Syngnathidae) - Magnus Wolf; Bruno Lopes da Silva Ferrette; Raphael T. F. Coimbra; Menno de Jong; Marcel Nebenführ; David Prochotta; Yannis Schöneberg; Konstantin Zapf; Jessica Rosenbaum; Hannah A. Mc Intyre; Julia Maier; Clara C. S. de Souza; et al. (GigaByte, 2024)
The snake pipefish, Entelurus aequoreus (Linnaeus, 1758), is a northern Atlantic fish inhabiting open seagrass environments that recently expanded its distribution range. Here, we present a highly contiguous, near chromosome-scale genome of E. aequoreus. The final assembly spans 1.6 Gbp in 7,391 scaffolds, with a scaffold N50 of 62.3 Mbp and L50 of 12. The 28 largest scaffolds (>21 Mbp) span 89.7% of the assembly length. A BUSCO completeness score of 94.1% and a mapping rate above 98% suggest a high assembly completeness. Repetitive elements cover 74.93% of the genome, one of the highest proportions identified in vertebrates. Our demographic modeling identified a peak in population size during the last interglacial period, suggesting the species might benefit from warmer water conditions. Our updated snake pipefish assembly is essential for future analyses of the morphological and molecular changes unique to the Syngnathidae.